The regions development characterisation by diversity/variety of the firms - study case for Romania - Cristina Lincaru; Mihaela Ghenţa; Draga Atanasiu; Vasilica Ciucă; Codruţa Drăgoiu; Beatrice Chiriac (European Regional Science Association (ERSA), 2010)
In this paper we try to find empirical evidence regarding the region diversity by firm characteristics, using spatial data from Tempo (INS Romania database) at NUTS 1, 2 and 3 region level for the period 1997-2008. Using instruments of statistical analysis of spatial data (Anselin, Varga) we try to sketch the spatial pattern of firm agglomerations and values of main firm's characteristics (size class according to employee's number and economic activity by NACE Rev.1 sections). Starting point is represented by the discussion made by Saviotti(*) regarding the efficiency vs diversity/variety in economic development respectively development versus growth. The pattern variation of the regions "profile" by diversity/variety of the firms could offer an image for the structural transformation of economic development tendencies of it in the last decade. (*) Pier Paolo Saviotti, INRA GAEL, Grenoble, and CNRS GREDEG I2C, Sophia Antipolis, France:"Is there a direction in economic development?", Pech, 2009
Keywords: 330